Patai's Chemistry of Functional Groups 2009
DOI: 10.1002/9780470682531.pat0012
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of the CF Bond: The Last Twelve Years

Abstract: Introduction Nucleophilic Fluorinating Reagents Electrophilic Fluorinating Reagents Synthesis of Compounds Containing The 18 F Isotope For Use In Positron‐Emitting Tomography Recent Reviews on Selective Fluorination Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 411 publications
0
2
0
Order By: Relevance
“…Halofluorination of unsaturated compounds is a versatile method to introduce fluorine and, in addition, a second reactive function into organic compounds. One of the most common procedures for bromofluorination uses N -bromosuccinimide (NBS) as the source of the bromonium ion and different amine−HF complexes. , A detailed account of regioselectivity of bromofluorination of functionalized olefins was provided by our research group a few years ago . Furthermore, Katzenellenbogen et al have previously demonstrated that bromofluorination could also serve as a radiochemical tool for introducing fluorine-18 into medicinally relevant compounds and thereby facilitate their use as imaging agents for PET. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Halofluorination of unsaturated compounds is a versatile method to introduce fluorine and, in addition, a second reactive function into organic compounds. One of the most common procedures for bromofluorination uses N -bromosuccinimide (NBS) as the source of the bromonium ion and different amine−HF complexes. , A detailed account of regioselectivity of bromofluorination of functionalized olefins was provided by our research group a few years ago . Furthermore, Katzenellenbogen et al have previously demonstrated that bromofluorination could also serve as a radiochemical tool for introducing fluorine-18 into medicinally relevant compounds and thereby facilitate their use as imaging agents for PET. …”
Section: Resultsmentioning
confidence: 99%
“…Halofluorination of unsaturated compounds is a versatile method to introduce fluorine and, in addition, a second reactive function into organic compounds. [41][42][43][44][45][46] One of the most common procedures for bromofluorination uses N-bromosuccinimide (NBS) as the source of the bromonium ion and different amine-HF complexes. 46,47 A detailed account of regioselectivity of bromofluorination of functionalized olefins was provided by our research group a few years ago.…”
Section: Resultsmentioning
confidence: 99%